NASKAH PUBLIKASI ANALISIS PENGARUH EARNING PER SHARE, RETURN ON ASSETS, RETURN ON EQUITY, DAN DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM (Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2013-2016) - AmiliaZubaidah, 14.05.52.0017; Sudiyatno, Bambang (Students' Journal of Accounting and Banking, 2018)
This study aims to determine the effect of Eearning Per Share, Return On Assets, Return On Equity, andDebt to Equity Ratioof stock return at manufacture company that listed in the Indonesia Stock Exchange at period 2013-2016. The sampling technique used was purposive sampling. The analytical tool was used is multiple regression analysis. Hypotheses test used t-statistic and f-statistic at level significant 5%. The result of this research show Return On Equity have a positive  significant effect to stock return. WhileEearning Per Share, Return On Assets, andDebt to Equity Ratiodon’t have significant effect to stock return. Result of this research indicate factor performance management in maximinizing their on capital (Return On Equity) used by investor to predict stock return of manufacture company that listed in the Indonesia Stock Exchange at period 2013-2016. Keywords : Eearning Per Share, Return On Assets, Return On Equity, Debt to Equity Ratio, Stock Return.